The Relationship Between Knowledge and Motivation of Pregnant Women with the Implementation of Integrated ANC at UPTD Plaosan Health Center - Dwi Yuniarti; Agung Suharto; Nuryani; Triana Septianti (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Antenatal care (ANC) is an important component in maternal health services to reduce maternal and infant mortality rates in Indonesia, which are still high. Every pregnancy in its development has a risk of complications, therefore ANC services must be carried out routinely, integrated, and according to quality antenatal service standards. In fact, not all pregnant women make regular ANC visits, so the coverage of K1, K4 and K6 is low, including at the Plaosan Health Center. The general objective of this study was to determine the relationship between knowledge and motivation of pregnant women with the implementation of Integrated ANC at UPTD Puskesmas Plaosan in 2024. The type of research used in this study was an analytic survey with a cross sectional design. Data analysis using primary data. The number of samples used was 37 pregnant women using purposive sampling technique. The independent variables in this study were knowledge and motivation while the dependent variable in this study was the implementation of integrated ANC. Data analysis was performed with chi-square test. The results showed that the variable of knowledge with the implementation of integrated ANC obtained significance with a p value = 0.014 while the motivation variable obtained a p value = 0.001 so that there is a significant relationship between knowledge and motivation with the implementation of integrated ANC. Therefore, knowledge and motivation need to be considered to be a reference in the implementation of integrated ANC..